Eye problems in children with hearing impairment - Ostadimoghaddam, Hadi (J Curr Ophthalmol, 2015)
PURPOSE: To compare the prevalence of refractive errors, amblyopia, and strabismus between hearing-impaired and normal children (7–22 years old) in Mashhad. METHODS: In this cross-sectional study, cases were selected from hearing-impaired children in Mashhad. The control group consisted of children with no hearing problem. The sampling was done utilizing the cluster sampling method. All of the samples underwent refraction, cover test, and visual examinations. RESULTS: 254 children in the hearing-impaired group (case) and 506 children in the control group were assessed. The mean spherical equivalent was 1.7 ± 1.9 D in the case group, which was significantly different from the control group (0.2 ± 1.5) (P < 0.001). The prevalence of hyperopia was 57.15% and 21.5% in deaf and normal children, respectively, but myopia was mostly seen in the control group (5.5% versus 11.9%, P = 0.007). The mean cylinder was 0.65 ± 1.3 D and 0.43 ± 0.62 D in deaf and normal subjects, respectively (P = 0.002). 12.2% of deaf subjects and 1.2% of normal subjects were amblyopic (P < 0.001), and the prevalence of strabismus was 3.1% in the case group and 2.6% in the control group (P = 0.645). CONCLUSION: In a comparison of children of the same ages, hearing-impaired children have significantly more eye problems; therefore, a possible relation between deafness and eye problems must exist. Paying attention to eye health assessment in hearing-impaired children may help prevent adding eye problems to hearing difficulties.